The Importance of Iron in the Regeneration of Skin and Cutaneous Wounds (International Journal of Food and Nutritional Sciences, 2022)
In this review paper, we explore the present state of information regarding the role that iron plays in the healing process of cutaneous wounds. Iron is an essential component in both the oxidative stress response as well as the photo-induced skin damage pathway. The ultraviolet (UVA) 320-400 nm region of the ultraviolet spectrum and physiologically accessible iron are the two primary contributors to oxidative stress in the skin. Reactive oxygen species (ROS) are also one of the primary causes of oxidative stress in the skin. In addition to this, we talk about the connections between iron deficiency, anaemia, and the healing of cutaneous wounds. There are two major categories to be found within this body of research. Early studies employed a range of experimental methods to determine anaemia or iron deficiency and concentrated on wound-strength rather than the influence of anaemia on macroscopic healing or re-epithelialization. These research were conducted to study the effect of anaemia on wound healing. In more recent investigations conducted on animals, innovative treatments have been examined with the goal of alleviating the effects of systemic iron deficiency as well as localised iron overload. Iron excess is associated with local cutaneous iron deposition, which is associated with multiple detrimental effects in both hereditary haemochromatosis and chronic venous illness. Anemia of chronic disease and dysregulation of local cutaneous iron haemostasis are associated with conditions such as rheumatoid arthritis (RA) and lupus erythematosus. Iron plays a key role in chronic ulceration, and conditions such as these are also associated with dysregulation of local cutaneous iron haemostasis. Iron is a potential therapeutic target in the skin by application of topical iron chelators and novel pharmacological agents, as well as in delayed cutaneous wound healing by treatment of iron deficiency or underlying systemic inflammation. This can be accomplished by applying iron chelators topically and utilising novel pharmacological agents.